A case series of concomitant burn and COVID-19. Issue 1 (January 2021) - Hesamirostami, Mohammadhossein; Nazarian, Roozbeh; Asghari, Hassan; Jafarirad, Abdolreza; Khosravi, Ali; Nouranibaladezaei, Seyedehzahra; Radfar, Azar
Highlights: Heightened inflammation and acute lung injury in major burn and COVID-19. Baseline comorbidities and possible worsening consequence. Medical management in concomitant burn and SARS-CoV-2 infection. Multidisciplinary approaches to manage coexisting diseases. Abstract: Background: The recently emerged severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) disease (COVID-19) has become a human pandemic. Heightened inflammation, vascular hyperpermeability, acute lung injury, coagulopathy, and cardiovascular abnormalities are among the SARS-CoV-2 infection-related complications. Major burn is also associated with metabolic derangements, vascular leak, and hemodynamic instability. Burn patients are at high risk for infections and developing sepsis. COVID-19 in burn victims might worsen the clinical outcome and make their medical management challenging. Result: Here, we present four cases of concomitant burn and COVID-19 with different degrees of complications. They had no (three out of four) or multiple (one out of four) baseline comorbidities and all were admitted to hospital for further management. Three out of four cases demonstrated acute respiratory failure and were intubated (no longer than 7 days). It seems that one of them had COVID-19 on arrival, the other apparently contracted at outside hospital, and the last two infected during the index hospitalization. Conclusion: Concomitant severe burn and COVID-19 might complicate the clinical presentation and hospital course. Such combination was associated with poor outcome in a case with baseline comorbidities, beyond what was expected from the severity of burn injury. However, a more comprehensive study with larger sample size is required to make a valid conclusion. With an ongoing COVID-19 global pandemic, SARS-CoV-2 infection might be a concurrent disease with other illnesses or traumas such as burn. This dictate multidisciplinary approaches to risk stratify, screen, assess, and manage coexisting diseases. Additionally, appropriate preparations and careful precautions need to be executed in burn units to prevent COVID-19 exposure and transmission to limit potential adverse outcomes.